Dendrochronology of Quercus ilex L. and its potential use for climate reconstruction in the Mediterranean region - Campelo, F.; Nabais, C.; García-González, I.; Cherubini, P.; GUTIÉRREZ, E.; Freitas, H. (Canadian Journal of Forest Research, 2009)
Holm oak (Quercus ilex L.) is a long-lived species widely distributed across the Mediterranean Basin, with potential value for dendrochronology and dendroclimatology. However, tree-ring dating in Q. ilex is a complex task that has limited the number of dendrochronological studies using this evergreen species. In the present work, it was investigated if old Q. ilex trees showed annual tree rings and whether they can be used as climate proxies. A long tree-ring chronology (126 years) of Q. ilex was developed using cross sections of 20 trees from the Guadiana river basin (Portugal). The high correlation among tree-ring series suggested that tree growth was controlled mainly by climate. Response function analysis showed a positive correlation between tree-ring width and precipitation from October(t–1) of the previous year to January(t) of the current year and in May(t). Tree-ring width was negatively correlated with the North Atlantic oscillation that exerts a strong influence on the precipitation over Iberia. Negative pointer years were triggered by dry years and became more frequent during the last decade of the 20th century. In conclusion, it is possible to accurately date old Q. ilex trees, and their tree rings could be used for climate reconstructions across the Mediterranean.
doi: 10.1139/X09-163doi: 10.1139/X09-163The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: climate reconstruction (PG); Dendrochronology; dendroclimatology; Quercus ilex

Dendrochronology of Quercus ilex L. and its potential use for climate reconstruction in the Mediterranean region - Campelo, F; Nabais, C; García-González, I; Cherubini, P; Gutiérrez, E; Freitas, H (Canadian Journal of Forest Research, 2009)
Holm oak (Quercus ilex L.) is a long-lived species widely distributed across the Mediterranean Basin, with potential value for dendrochronology and dendroclimatology. However, tree-ring dating in Q. ilex is a complex task that has limited the number of dendrochronological studies using this evergreen species. In the present work, it was investigated if old Q. ilex trees showed annual tree rings and whether they can be used as climate proxies. A long tree-ring chronology (126 years) of Q. ilex was developed using cross sections of 20 trees from the Guadiana river basin (Portugal). The high correlation among tree-ring series suggested that tree growth was controlled mainly by climate. Response function analysis showed a positive correlation between tree-ring width and precipitation from October(t–1) of the previous year to January(t) of the current year and in May(t). Tree-ring width was negatively correlated with the North Atlantic oscillation that exerts a strong influence on the precipitation over Iberia. Negative pointer years were triggered by dry years and became more frequent during the last decade of the 20th century. In conclusion, it is possible to accurately date old Q. ilex trees, and their tree rings could be used for climate reconstructions across the Mediterranean.
doi: 10.1139/X09-163
Keywords: climate reconstruction (PG); Dendrochronology; dendroclimatology; Quercus ilex

Influence of Climate on Radial Growth of Holm Oaks (Quercus Ilex Subsp. Ballota Desf) from SW Spain - Patón, Daniel; García-Herrera, Ricardo; Cuenca, Javier; Galavis, Mamen; Roig, Fidel (Geochronometria, 2009)
A total of 47 trunk sections from Holm Oak (Quercus ilex subsp. ballota Desf) trees growing at two different sites at the Extremadura region (SW Spain) were considered in the computation of a regional tree-ring chronology useful to interpret the tree-ring/Mediterranean climate relationships. This is the first dendroclimatological research of Holm Oaks conducted to reveal its potential use as a climatic proxy. The obtained tree-ring chronologies were compared with climatic parameters based on monthly, seasonal and annual rainfall, and monthly maximum, minimum and average temperature. The best correlations were obtained with maximum temperatures during the period between previous winter and early spring. Influence of rainfall was less relevant. Growth of this species indicates a typical bimodal (spring and autumn) strategy that avoids low winter temperatures and summer drought. Despite some technical difficulties recognizing tree rings in Holm Oaks, its good sensitivity to climate variability and its wide distribution and longevity (~800 years), allow us to consider this species as a good candidate for temperature reconstructions in the Mediterranean Basin.
Keywords: climatic change; Dendrochronology; dendroclimatology; Extremadura; maximum temperature; Quercus ilex; Spain; tree rings

Influence of Climate on Radial Growth of Holm Oaks (Quercus Ilex Subsp. Ballota Desf) from SW Spain - Patón, Daniel; García-Herrera, Ricardo; Cuenca, Javier; Galavis, Mamen; Roig, Fidel (Geochronometria, 2009)
A total of 47 trunk sections from Holm Oak (Quercus ilex subsp. ballota Desf) trees growing at two different sites at the Extremadura region (SW Spain) were considered in the computation of a regional tree-ring chronology useful to interpret the tree-ring/Mediterranean climate relationships. This is the first dendroclimatological research of Holm Oaks conducted to reveal its potential use as a climatic proxy. The obtained tree-ring chronologies were compared with climatic parameters based on monthly, seasonal and annual rainfall, and monthly maximum, minimum and average temperature. The best correlations were obtained with maximum temperatures during the period between previous winter and early spring. Influence of rainfall was less relevant. Growth of this species indicates a typical bimodal (spring and autumn) strategy that avoids low winter temperatures and summer drought. Despite some technical difficulties recognizing tree rings in Holm Oaks, its good sensitivity to climate variability and its wide distribution and longevity (~800 years), allow us to consider this species as a good candidate for temperature reconstructions in the Mediterranean Basin.
Keywords: climatic change; Dendrochronology; dendroclimatology; Extremadura; maximum temperature; Quercus ilex; Spain; tree rings

Influence of climate on the seasonality of radial growth of cork oak during a cork production cycle - Costa, Augusta; Pereira, Helena; Oliveira, Ângelo (Ann. For. Sci., 2002)
The radial growth of mature cork oaks (Quercus suber L.) was studied during a 9-year production cycle using monthly dendrometer measurements and cork ring widths. The mean tree radial increase was 5.1 mm yr -1 and the cork increment accounting for 3.8 mm yr -1. The radial growth curves for cork, wood and stem were very similar, showing a decreasing trend along the production cycle. Cork increment was always the largest fraction of tree growth (on average 74%) and showed less inter-annual variations as compared to wood. Tree radial growth presented a clear within-the-year seasonal pattern, extending from March to October, with a maximum in June-July. The overall pattern of monthly growth distribution was similar among the years of the production cycle, but some inter-annual variations occurred with 1-2 month shifts or monthly growth rate decreases, related to climatic factors. Early spring growth was enhanced by winter rain, autumn growth by high summer rain and June increments by high temperatures during this month.
Keywords: climatic fluctuations; cork growth; Cork oak; dendroclimatology; diameter growth

Influence of climate on the seasonality of radial growth of cork oak during a cork production cycle - Costa, Augusta; Pereira, Helena; Oliveira, Ângelo (Ann. For. Sci., 2002)
The radial growth of mature cork oaks (Quercus suber L.) was studied during a 9-year production cycle using monthly dendrometer measurements and cork ring widths. The mean tree radial increase was 5.1 mm yr -1 and the cork increment accounting for 3.8 mm yr -1. The radial growth curves for cork, wood and stem were very similar, showing a decreasing trend along the production cycle. Cork increment was always the largest fraction of tree growth (on average 74%) and showed less inter-annual variations as compared to wood. Tree radial growth presented a clear within-the-year seasonal pattern, extending from March to October, with a maximum in June-July. The overall pattern of monthly growth distribution was similar among the years of the production cycle, but some inter-annual variations occurred with 1-2 month shifts or monthly growth rate decreases, related to climatic factors. Early spring growth was enhanced by winter rain, autumn growth by high summer rain and June increments by high temperatures during this month.
Keywords: climatic fluctuations; cork growth; Cork oak; dendroclimatology; diameter growth

A dendroclimatological approach to diameter growth in adult cork-oak trees under production - Costa, A.; Pereira, H.; Oliveira, A. (Trees, 2001)
The diameter growth of mature cork oaks under cork production in southwestern Portugal was studied during a 9-year cork-production cycle in relation to fluctuations in precipitation and temperature, and to drought indices combining the two variables. A dendroclimatological approach was applied to the series of 8 complete years contained in the cork-production cycle and growth effects were removed by standardization and calculation of annual growth indices. The most important factor positively influencing diameter growth was cumulative precipitation in the growing season (January–June) and in the previous autumn and winter (October/November of the previous year–June). The monthly temperature is a less influential factor, negatively correlated with diameter growth in high summer drought (August) and positively correlated at the beginning of physiological activity (March).
Keywords: climatic fluctuations; dendroclimatology; diameter growth; Mediterranean climate; Quercus suber L.

Influence of weather on cork-ring width - Caritat, Antònia; Gutiérrez, Emilia; Molinas, Marisa (Tree Physiology, 2000)
Ring-width series of cork from Quercus suber L. trees growing at two sites in Extremadura (southwestern Spain) were analyzed in relation to monthly precipitation and temperature, and to climatic indices combining both variables. Ring width of cork showed strong positive correlations with precipitation, especially during the fall and winter. Moderately low temperatures were favorable for cork growth, except in winter and during the onset of phellogen activity. We conclude that drought or temperature, or both, can limit cork growth during the annual drought period.
10.1093/treephys/20.13.893
Keywords: climatic variability; cork growth; cork-ring chro- nology; dendroclimatology; phellogen activity; Quercus suber

Influence of weather on cork-ring width - Caritat, Antònia; Gutiérrez, Emilia; Molinas, Marisa (Tree Physiology, 2000)
Ring-width series of cork from Quercus suber L. trees growing at two sites in Extremadura (southwestern Spain) were analyzed in relation to monthly precipitation and temperature, and to climatic indices combining both variables. Ring width of cork showed strong positive correlations with precipitation, especially during the fall and winter. Moderately low temperatures were favorable for cork growth, except in winter and during the onset of phellogen activity. We conclude that drought or temperature, or both, can limit cork growth during the annual drought period.
10.1093/treephys/20.13.89310.1093/treephys/20.13.893
Keywords: climatic variability; cork growth; cork-ring chro- nology; dendroclimatology; phellogen activity; Quercus suber